2022
DOI: 10.3390/fishes8010007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Blend of Algae Extract Supplementation on Growth, Biochemical, Haemato-Immunological Response, and Immune Gene Expression in Labeo rohita with Aeromonas hydrophila Post-Challenges

Abstract: In this study, the effects of a mixed algal blend (Chlorella vulgaris, Euglena viridis, and Spirulina platensis) at different levels were evaluated on growth, hematological immune responses, and expression of immune genes in Labeo rohita against post-challenges of Aeromonas hydrophila. Fish samples were fed a diet containing different levels of mixed blend algal (0, 0.01, 0.02, 0.04 and 0.08% of basal diet). At the end of the feeding period, the fish were challenged with A. hydrophila and fish mortality was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 72 publications
5
14
0
Order By: Relevance
“…The search for natural alternatives to growth and immunity promoters in aquaculture has been spurred by the need for safe, organic, and healthful food on a global scale (Ashour et al, 2021). Microalgae have become a more affordable and ecologically friendly alternative source of almost all the nutrients that sh need due to the rise in sh production in recent years (Sattanathan et al, 2022). Minerals, antioxidants, proteins, lipids, pigments, and numerous bioactive compounds are all abundant in algae (Peixoto et al, 2019;Safavi et al, 2019;Sajina et al, 2019;Sharawy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The search for natural alternatives to growth and immunity promoters in aquaculture has been spurred by the need for safe, organic, and healthful food on a global scale (Ashour et al, 2021). Microalgae have become a more affordable and ecologically friendly alternative source of almost all the nutrients that sh need due to the rise in sh production in recent years (Sattanathan et al, 2022). Minerals, antioxidants, proteins, lipids, pigments, and numerous bioactive compounds are all abundant in algae (Peixoto et al, 2019;Safavi et al, 2019;Sajina et al, 2019;Sharawy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The bene cial effects of algal bioactive compounds on the growth performance of different sh species have been shown in earlier research. As an example, in a study by Sattanathan et al (2022), it was observed that the growth performance of rohu carp (Labeo rohita) improved when fed diets enriched with Chlorella vulgaris, Euglena viridis, and Spirulina platensis. Based on the ndings of Ashour et al (2020), the growth performance of Nile tilapia was signi cantly enhanced when fed diets containing a 2% level of commercial liquid seaweed extract (TAM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced growth performance, health, nutritional performance, and coloration have been declared with dietary small amounts of microalgae inclusion (1-5%) in a range of fish species [72,73]. Spirulina is a microalga commercially used as a supplementary food in human nutrition and finfish diets due to its rich source of protein, indispensable fatty acids, essential amino acids, vitamins, and minerals [72,[74][75][76]. The effects of dietary Spirulina on the growth performance and skin coloration have been studied for ornamental finfish species, including red swordtail, Xiphophorus helleri [77], goldfish, Carassius auratus [78,79], yellow tail cichlid, Pseudo tropheusacei [72], and three-spot gourami, Trichopodus trichopterus [80].…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate state, which is associated with inadequate water quality, malnourishment, and other related factors, is non-communicable in fish. Non-communicable diseases encompass a range of conditions that may arise due to factors such as hyper aeration, inadequate nutrient intake (including vitamin and mineral deficiencies), exposure to industrial and agricultural pollutants, genetic mutations, and neoplastic anomalies, which involve abnormal growth and development of organs resulting in their structural and functional impairment [ 1 , 2 , 3 , 4 ]. The alternative form of ailment is pathogenic in nature and is believed to be especially deleterious due to its propensity for transmission between fish, ultimately leading to substantial mortality rates.…”
Section: Introductionmentioning
confidence: 99%